2018
DOI: 10.11648/j.jppa.20180203.13
|View full text |Cite
|
Sign up to set email alerts
|

Financial Forecasting by Autoregressive Conditional Heteroscedasticity (ARCH) Family: A Case of Mexico

Abstract: Understanding and modeling the volatility measurements is important for forecasting the risk and for evaluating asset allocation decisions of stock market. The study have used the daily frequency data from January 1, 2002 to September 30, 2016 as an in-sample period to perform empirical analyses for modeling and predicting the volatility dynamics of Mexican stock market (IPC). To facilitate the variance forecast, the competing models are ARCH (p, q), GARCH (p, q), and its variations i.e. Glosten Jagnnathon Run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Research [14] explained that the forecasting model with GARCH obtained statistically significant results compared to other volatility forecasting models such as MLP, GRNN, GMDH, RF, QRRF, and QRNN on eight financial data sets. It was also found that ARCH / GARCH could be used to study voltages in other fields such as agriculture ( [15] & [16]), and gold by [17]- [26] are similar in relation to the use of the ARCH / GARCH method in dealing with the symptoms of volatility. and [27].…”
Section: Introductionmentioning
confidence: 91%
“…Research [14] explained that the forecasting model with GARCH obtained statistically significant results compared to other volatility forecasting models such as MLP, GRNN, GMDH, RF, QRRF, and QRNN on eight financial data sets. It was also found that ARCH / GARCH could be used to study voltages in other fields such as agriculture ( [15] & [16]), and gold by [17]- [26] are similar in relation to the use of the ARCH / GARCH method in dealing with the symptoms of volatility. and [27].…”
Section: Introductionmentioning
confidence: 91%
“…al. [7] use the daily frequency data from 2002 to 2016 as an in-sample period to perform empirical analyses for modelling and predicting the volatility dynamics of the Mexican stock market (IPC). Kim and Won [8] propose a new LSTM model and combine it with multiple GARCH-type models to forecast the volatility of the stock price index using KOSPI 200 index data.…”
Section: Existing Researchmentioning
confidence: 99%